Acculturation and depressive symptoms in latino caregivers of cognitively impaired older adults. (September 2014) - Meyer, Oanh L.; Geller, Sue; He, Emily; González, Hector M.; Hinton, Ladson
ABSTRACT Background: Caregiving for older adults is a growing public health concern because of the negative psychological effects it has on caregivers. Despite the growing Latino caregiver population, little is known regarding how the effects of acculturation on caregiver depressive symptoms might vary by caregiver age. This study aimed to examine the relationship between language acculturation and depressive symptoms in Latino caregivers, and to test whether this relationship was moderated by age. Methods: Ninety-four Latino caregivers of cognitively impaired older adults with and without dementia were identified through an ongoing epidemiological cohort study. Caregivers were interviewed in their homes, in either Spanish or English. A Poisson regression was used to analyze the caregiver characteristics associated with caregiver depressive symptoms. Results: Language acculturation was positively associated with caregiver depressive symptoms, as was age, female gender, and being married or living with someone. Those with excellent or good health and who had spent more than one year caregiving had lower depressive symptoms. Finally, the positive relationship between language acculturation and depressive symptoms was increased in older caregivers. Conclusions: Language acculturation appears to be a risk factor for depressive symptoms in Latino caregivers of cognitively impaired older adults. The relationship between language acculturation and depressive symptoms is complex such that caregiver age and health status further nuance this relationship. Future research should explore the independent and interactive effects of these variables on depressive symptoms.